A student athlete's guide to college success peak performance in class and life - Petrie, Trent (Wadsworth Publishing Company, 1999)
This text features coverage of mainstream college success topics with a special focus on student-athletes. Included are chapters on motivation and procrastination, health and performance, and communication and assertiveness, as well as special boxes on media relations and the transferability of skills from athletics to academic courses.